Pengaruh Efektivitas Informasi Akuntansi Manajemen Terhadap Pengambilan Keputusan Manajemen Pada PT. PDAM Way Rilau Bandar Lampung - Angrita Denziana; Erlin Handayani (Universitas Bandar Lampung (UBL), 2015)
The purpose of this study was to determine the effect of the effectiveness of managementaccounting information on PT PDAM Way Rilau Bandar Lampung and relationship management accounting information in management decision making PT PDAM Way Rilau Bandar Lampung. Effective management accounting information in the study that determined19 criteria for effectiveness : is in the type and frequency of reports in accordance with the requirement : accurate, timely, reliable, have predictive value. Is an accountability report, easy to understand, not biased, has been complemented by the necessary comments, consistent. Is there any influence between the information accounting management against management decision making. These results indicate that all of the information generated effective management accounting or have met the criteria for effectiveness.